NSCT DOMAIN BASED MULTIMODAL MEDICAL IMAGE FUSION APPROACH BASED ON PHASE CONGRUENCY AND DIRECTIVE CONTRAST (International Journal of Engineering and Computer Science, 2015)
Although tremendous progress has been made in the medical image processing in past decade for evaluation of the clinical information based on obtained medical images, still there exist a number of problems. In medical image processing some advert cases of clinical analysis have been recorded where physician fails to analyze the patient scenario based on single medical source image. In this paper a novel medical image fusion work based on NSCT domain has been presented which proves to be efficient than conventional approaches. In conventional algorithms no relevant research has been carried out to get detailed low frequency and high frequency coefficients which helps further in reliable fusion process. In proposed method phase congruency and directive contrast are used to yield reliable analytical analysis of low frequency and high frequency coefficients. Finally reconstructed fused image has been proposed based on acquired composite coefficient. In experimental results performance gain of proposed method can be clearly seen over the conventional approaches and this multimodal fusion approach has been successfully conducted on Alzheimer, subacute stroke and recurrent tumor which shows clinical ability of the proposed method in terms of good accuracy and better performance. In extension is done on YCBCR color space for better analysis.